THINKING CONTEMPORARY FACTORIAL POLITICAL FLUX & POLARIZATION ISSUES TO PAKISTAN’S GOVERNMENT: (A PANORAMIC APPRAISAL) - NISAR, RANA DANISH; AROOJ (The journal of contemporary issues in business and government, 2022)
The current inscription allows the readers to comprehend the existing political issues of Pakistan. Pakistan has experienced in-depth political instability and polarization for many years, with frequent changes in government, fall of democratic elected bodies and a long history of almost three time military coups. In very recent years, these challenges have been compounded by intemperate political tensions, ethnic rigidities as well as rise of immoderate political and social intolerance. Political polarization is also a major concern, with political parties and factions often divided along ideological and ethnic lines, making it difficult to achieve consensus on important issues. These severe challenges have hampered Pakistan’s economic growth and social development, and have made it more difficult to address issues such as poverty, corruption, unemployment, lack of national integration, deficiency of peaceful co-existence, shortage of tolerance either political or social and terrorism. Despite these challenges, Pakistan remains an important regional political player, and efforts are underway to address these issues through political and social reforms, as well as through engagement with the global community for win-win standpoint. This present scholarship is qualitative in nature along with analytical and descriptive sermon.